Pendampingan Pengelolaan Pajak Pada Kelompok Pengerajin Songket di Desa Muara Penimbung Ulu - Muhammad Hidayat; Lukluk Fuadah; Abdullah Saggaf; Muhammad Ichsan Siregar; Ery Erman (Jurusan Akuntansi Fakultas Ekonomu Universitas Sriwijaya, 2022)
The main problem for MSMEs in fulfilling tax obligations is a lack of knowledge and adequate human resources in completing administration in the taxation field. The purpose of this service is to provide assistance in tax management using tax application provided by the DJP. The method of implementing this service is socialization in the form of presentations to MSMEs and assistance in the use of tax applications to MSME employees in Desa Muara Penimbung Ulu City. The result of this service is an increase in MSME understanding of taxation and an increase in the ability of MSMEs to use applications in the field of taxation